Born nude - Mhango, Nkwazi Nkuzi (Langaa RPCIG, 2019)
Born Nude is philosophical poetry that explores myriad themes, from equality to humility and environmental consciousness. It is divided into chapters that pinpoint specific areas of interest. The author delves into human weaknesses and strengths based on nature and nurture. He invites the reader to contemplate the ephemeral nature of all things material, and how to nurture oneself into a higher order and loyalty of being human. The volume's satirical tone is critical of the destructive sterility of zero-sum games of superiority and dominance. It treats as anathema exploitation based on contrived hierarchies of gender, geography, politics and the geopolitik of the modern world.